The relationship between perception and landscape characteristics of recreational places with human mental well-being - Janina Vanhöfen; Talia Härtel; Giovanna Reichert; Christoph Randler (Scientific Reports)
Abstract Being outdoors benefits both humans’ physical and mental well-being, but the reasons for this connection are difficult to pinpoint. This study examines 40 recreational areas to understand their individual characteristics’ impact on mental well-being. We interviewed 1184 visitors on their perception of the place and feeling of mental well-being. In a second survey, 49 participants were shown images of the areas to assess whether they perceived them in the same way as people on-site did. Biologists then evaluated the areas through bird and biotope surveys, also assessing various other landscape characteristics of the study areas. Analysis using a two-level multivariate GLM revealed that perceived naturalness and perceived bird diversity are significant predictors of improved mental well-being. On the flip side, mental well-being declines with increased human impact, as indicated by the amount of infrastructure and the Human Footprint Index value. Notably, perceived naturalness positively correlates with actual bird diversity (p = 0.005) and negatively with human impact (p = 0.006). A strong perception of birds enhances the mental well-being of greenspace visitors (p < 0.001), while a high birding specialization negatively affects recalled restoration (p = 0.014). The estimated restoration value (p = 0.001) and estimated beauty (p < 0.001) from the online survey correlate positively with emotions experienced on-site. The perception of naturalness in images aligns with on-site perception, suggesting pathways for future research and the design of recreational areas.